PENGARUH HUKUM TERHADAP OBAT GENERIK, PERSPEKTIF UNDANG-UNDANG KESEHATAN DAN UNDANG-UNDANG PATEN - I Komang Agus tri Wismantara; Ety Isworo; Lalu Mahmud Yasin (Universitas Duta Bangsa Surakarta, 2025)
ABSTRACT The legal regulation of generic drugs in Indonesia is a complex and multidimensional issue, involving the interaction between the Health Law and the Patent Law. This study aims to analyze how these two laws interact in regulating the production, distribution, and accessibility of generic drugs. Using current data and statistics, as well as relevant case studies, this research reveals the impact of these regulations on drug accessibility for the public, especially for low-income groups. The research findings indicate that while the Health Law provides a legal basis for improving drug accessibility, the Patent Law often acts as an obstacle that complicates the situation. Keywords: Generic drugs, Health Law perspective, Patent Law